2021
DOI: 10.18203/issn.2455-4510.intjresorthop20211894
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-radiological and functional outcomes of bicolumnar plating in schatzker type 5 and type 6 fractures of proximal tibia in tertiary care hospital in North India: a series of 26 patients

Abstract: <p class="abstract"><strong>Background:</strong> Ideal mode of treatment is always debatable for Schatzker type 5 and type 6 fractures in proximal tibia. The aim of the study was management in tibial plateau fracture are to obtain anatomic reduction of the articular surface, restoration of axial alignment, and achieve stable fixation which can be done by open reduction and internal fixation (ORIF) using bicolumnar plating.</p><p class="abstract"><strong>Methods:</strong&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…their study, Zhang et al found that 89.9% of cases had RTA injuries 10 , whileKumar et al found that all cases (100%) had RTA 11. Studies conducted by Ghani et al also corroborate the male preponderance 12. …”
mentioning
confidence: 86%
“…their study, Zhang et al found that 89.9% of cases had RTA injuries 10 , whileKumar et al found that all cases (100%) had RTA 11. Studies conducted by Ghani et al also corroborate the male preponderance 12. …”
mentioning
confidence: 86%